If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + (-13 + -5x) = -13 Remove parenthesis around (-13 + -5x) 5x + -13 + -5x = -13 Reorder the terms: -13 + 5x + -5x = -13 Combine like terms: 5x + -5x = 0 -13 + 0 = -13 -13 = -13 Add '13' to each side of the equation. -13 + 13 = -13 + 13 Combine like terms: -13 + 13 = 0 0 = -13 + 13 Combine like terms: -13 + 13 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| .50x^2-5=5 | | X-2[1-3(2x+4)]=61 | | 4x+8-x=17 | | 4+2x-3=12 | | 2+(8+4x)=14 | | 12x-4y=16 | | 3(x+4)+3=9 | | 6x+15y=5 | | 8x+2y=-1 | | 5x-10y=-20 | | y+6=20+5 | | 4x^2-31x-8=0 | | 5a+4(3a-8)=4+3a | | 8b+2b-4=6 | | 6x+(2x-4)=12 | | 10z-21=9z+10 | | g(x)=2x-6g(2x) | | 4x=1000000 | | 2z^2-3z=7 | | 9(a+1.46)+8(b-16a)= | | 2(10-6n)=x-8x | | 8-3y=7y-2-5y | | -2(5s-4)-8=-2(7s+7)-2 | | 8(3x-5)=10x+2 | | 1.9=w+0.42 | | 2x+4=5x-14 | | 3(5x-3)-8(x-1)= | | 3+x=2 | | 6*x^2-2*x=0 | | 8m=24 | | x^2+4x+xz= | | 13x-2(6x-4)=72 |